The Relationship of CSR Strategy Towards Organizational Sustainability: The Moderating Effect of Political CSR - Indah Kurniawaty; Fadhilah Fadhilah; Sarfilianty Anggiani (Green Publisher Indonesia, 2025)
This paper aims to determine the moderating role of political CSR in shaping a company's CSR strategies towards achieving organizational sustainability. Using a qualitative approach and case study design with a content analysis method derived through a combination of interactive and documentative analysis models. The analysis reveals that in the case of CSR programs implemented by upstream oil and gas companies on Madura Island, a strong influence of political interests significantly weakens the relationship between the company's CSR strategy and organizational sustainability.